Quality of life of persons with complete traumatic spinal cord injuries in Gaborone and surrounding areas: a qualitative enquiry - Kwadiba, Beauty (Stellenbosch : Stellenbosch University, 2017)
Thesis (MHumanRehabSt)--Stellenbosch University, 2017.